Rapport in the Foreign Language Classroom: From Face-to-Face to Online in Times of Pandemic - Katz, Shayna (Íkala, Revista de Lenguaje y Cultura, 2021)
As shown in previous studies, positive teacher and student rapport increases motivation and performance in foreign language learning. This study investigated the impact of three forms of interaction on the development of teacher-student and student-student relationships in a Spanish as a Foreign Language classroom that transitioned from face-to-face (FtoF) to online due to the emergence of the covid- 19 pandemic. These forms of interaction were positive comments, corrective feedback, and personal thematic discourse. The participants were students from six different beginner-level Spanish courses at a university in Hawai’i. Because of covid restrictions, half of the semester was conducted FtoF and half online. Data were collected through a three-part questionnaire with open and closed-ended questions which explored the impact of the online and FtoF setting and forms of interaction on rapport. The results reveal the importance of corrective feedback and positive comments on the development of positive teacher-student rapport, and of positive comments and personal thematic discourse on student-student rapport. The study suggests the need to bring qualities from the FtoF classroom to online, such as a sense of a more personal experience, ability to connect, ease in asking questions, receiving feedback, and greater interaction.